The Impact of Pension Age Changes – The Case of Malta - Aaron G. Grech (Intereconomics, 2017)
After remaining unchanged for several decades, the pension age in Malta started to rise in 2012. This process, which will continue until 2026, was introduced to help boost the workforce and partially countervail the impact of the country's demographic transition. The scope of this article is to review evidence on the impact to date of these changes and to use this to try to understand the potential impact of remaining pension age changes.
Keywords: 330